Świat poezji Ełły Krylowej - Nikadem-Malinowska, Ewa (Acta Polono-Ruthenica, 2006)
Ella Krylova belongs to the generation of Russian poets whose creative path started almost simultaneously with the birth of new Russia. Today she is the author of over ten poetry collections, she regularly publishes her poems on the Internet, she is well-known abroad. She is searching for her own form of expression, adequate to the thought which can be ironic or philosophical, but always present in the words. Her oversensitive lyrical ego, listening carefully to the world problems, fights with adversities with the help of irony. The world of her poetry is deeply humane, it is the world of universal values and spiritual rebirth of man.